PENGARUH KONSELING APOTEKER TERHADAP TINGKAT KEPATUHAN MINUM OBAT DAN KADAR GULA DARAH PASIEN DIABETES MELLITUS - Rahmawaty, Annis; Anggraeni, Nanda Widia (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
Background: Diabetes mellitus is a metabolic disorder characterized by high blood sugar levels. The level of adherence to taking medications plays a very important role in achieving successful treatment and maintaining blood sugar levels within normal ranges, as well as pharmacist counseling is very important in handling DM. Objective: The purpose of this study was to determine the effect of pharmacist counseling on the level of adherence to taking oral antidiabetic drugs in diabetes mellitus patients at the Ngembal Kulon Kudus Health Center. Method: This study is a pre-experimental study designed by One Group Pretest Posttest with cross-sectional data retrieval. Data collection was carried out in March-April 2022 at the Ngembal Kulon Kudus Health Center. Result: This study used spearman correlation test with 0.000 results obtained, wilcoxon test obtained 0.000 results and the paried T-test obtained results of 0.000 which were said to be significantly different before and after pharmacist counseling. Conclusion: Counseling there was a change in compliance in diabetes mellitus patients there was an effect of providing pharmacist counseling on the level of adherence to taking oral antidiabetic drugs using the MGL MAQ questionnaire (p 0.000) and blood sugar levels in demographic data (p 0.000) in diabetes mellitus patients.